First evaluation of the emotional picture set of self-injury images (EPSI) using psychophysiological and self-report measures - Sarah-Louise Unterschemmann; Erik Malte Mueller; Silke Lux; Alexandra Philipsen; Marcel Schulze (Borderline Personality Disorder and Emotion Dysregulation)
Abstract Background Nonsuicidal self-injury (NSSI) has been identified as one of the most important predictors of suicidal ideation and attempts. Nevertheless, previous research on NSSI has been limited, with different experimental designs leading to inconsistent findings regarding its underlying factors. This is especially true for time-related processes of NSSI. To address this, a standardized set of symptom-specific emotional stimuli was developed (Emotional Picture Set of Self-Injury Images, EPSI), depicting differing stages of NSSI. This study offers a first evaluation of the EPSI picture set as a measurement of emotional reactivity by using emotional self-reports and psychophysiological measures in a sample of healthy participants. Method The EPSI picture set, which includes images with neutral objects, self-injury objects, and self-injury scenes, was presented to N = 64 (age: 22.42 (1.4) years, sex: 18 m/ 46f) healthy participants. Emotional reactivity was assessed using emotional self-reports (Self-Assessment Manikin, SAM-Rating) for valence and arousal dimensions. Additionally, psychophysiological measures including skin conductance response, heart period, and the acoustic evoked startle response were recorded. Results Overall, the intraclass correlation coefficient and item-total correlation were sufficiently high, indicating good reliability at both the picture and category level. Participants rated self-injury pictures as significantly more unpleasant and arousing compared to pictures showing objects of self-injury and neutral objects. The skin conductance response to pictures with scenes of self-injury was significantly increased compared to pictures with neutral objects, as was heart period deceleration. Conclusions This initial evidence suggests that EPSI elicits distinct emotional responses and may serve as a valid measure for studying the process of NSSI. Future research could investigate the EPSI as a standardized measure, particularly in patients with NSSI and borderline personality disorder, to validate its clinical utility and gain insight into its psychophysiological mechanisms.